2019
DOI: 10.3201/eid2512.191143
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H1N1)pdm09 Virus Infection in a Captive Giant Panda, Hong Kong

Abstract: We report influenza A(H1N1)pdm09 virus infection in a captive giant panda in Hong Kong. The viral load peaked on day 1 and became undetectable on day 5, and an antibody response developed. Genome analysis showed 99.3%–99.9% nucleotide identity between the virus and influenza A(H1N1)pdm09 virus circulating in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…pdm09 are maintained at protective levels (greater than or equal to 32HI) for up to 15 months after a single influenza infection (Sridhar et al, 2015). Although we could not rule out the possibility that the cheetahs were pre-exposed to the virus, our findings showed that cheetahs naturally infected with influenza virus maintained detectable levels of antibodies for at least 10 months ( Table 2) pdm09 virus infection has been reported in a variety of captive wild animals including threatened species such as giant pandas (VU) (Li, Zhu, et al, 2014;Martelli et al, 2019), a sloth bear (Melursus ursinus) (VU) (Boedeker et al, 2017) and a black-footed ferret (Mustela nigripes) (endangered animal, EN) (Schrenzel et al, 2011). More recently, serological evidence of influenza virus infection was found in tigers (EN) and…”
Section: Discussionmentioning
confidence: 76%
“…pdm09 are maintained at protective levels (greater than or equal to 32HI) for up to 15 months after a single influenza infection (Sridhar et al, 2015). Although we could not rule out the possibility that the cheetahs were pre-exposed to the virus, our findings showed that cheetahs naturally infected with influenza virus maintained detectable levels of antibodies for at least 10 months ( Table 2) pdm09 virus infection has been reported in a variety of captive wild animals including threatened species such as giant pandas (VU) (Li, Zhu, et al, 2014;Martelli et al, 2019), a sloth bear (Melursus ursinus) (VU) (Boedeker et al, 2017) and a black-footed ferret (Mustela nigripes) (endangered animal, EN) (Schrenzel et al, 2011). More recently, serological evidence of influenza virus infection was found in tigers (EN) and…”
Section: Discussionmentioning
confidence: 76%
“…11 While the cheetah, the Bornean binturong, the American badger, and the giant panda exhibited severe respiratory signs of infection-hematopnea and dyspnea-no clinical signs were reported in the black-footed ferret. 11,29,58 Besides in zoo carnivores, there was evidence of pH1N1 virus infection in Asian elephants (Elephas maximus) based on the presence of pH1N1 antibodies. The source of infection remains unknown, but most likely was infected mahouts, or infected tourists who attended activities such as elephant riding and feeding.…”
Section: Petsmentioning
confidence: 99%
“…Several zoo carnivores including a cheetah ( Acinonyx jubatus ), a Bornean binturong ( Arctictis binturong penicillatus ), an American badger ( Taxidea taxus ), a black-footed ferret ( Mustela nigripes ), and a giant panda ( Ailuropoda melanoleuca ) were susceptible to pH1N1 virus infection. 11 , 29 , 58 The source of infection in these cases was not determined due to lack of availability of clinical samples from humans with close contact. However, all affected animals were in contact with caretakers or veterinarians, and were housed separately from other wildlife.…”
Section: Pandemic H1n1 Influenzamentioning
confidence: 99%
See 2 more Smart Citations